(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the most crucial facets of teacher welfare is the quality of teacher-student relationships (TSRs), which has been demonstrated to predict a range of academic as well as social, emotional, and behavioral outcomes for teenage students. Consequently, because they shed light on the caliber of these interactions, TSR measurements are crucial for educational institutions. The significance of TSRs has been explained by a variety of theoretical frameworks; nonetheless, conceptions of TSRs in the literature have mostly concentrated on Western civilizations. Therefore, the goal of this study was to investigate the various ways that TSRs are conceptualized in different cultural contexts by looking at the items on student and teacher-reported measures of teenage TSRs.25 rating scale measures of TSRs that had been especially created and approved for use with teenagers in Asia, Europe, and North America were found through a review of the literature. Six key themes emerged from thematic analysis that are pertinent to teenage TSRs: classroom management, instructional strategies, positive student attributes, classroom climate, negative interpersonal interactions, and positive teaching attributes. However, the conceptualization of these issues differed by area.